The effectiveness of supervised exercise training regarding NT-pro BNP level as a prognostic value among patients with congenital heart disease-related to pulmonary hypertension - Setyowati, Danti Utami; Martini, Heny; Prasetya, Indra (Universitas Brawijaya, 2025)
Congenital heart disease-related to pulmonary hypertension (CHD-PH) constitutes a significant subset of related Pulmonary Hypertension (PH), representing around 11% of all PH patients. Considering the emergence of novel medicines and enhanced patient outcomes in PH, it continues to be a life-shortening condition, and the time frame before diagnosis has not altered. Current strategies to enhance outcomes emphasize on early diagnosis and a treatment methodology designed to put individuals with PH into a low-risk category for one-year mortality. The N-terminal prohormone of BNP (NT-pro BNP) is secreted by cardiomyocytes in reaction to mechanical strain and wall stress. An increased concentration of NT-pro BNP is included in some PH risk stratification methods and screening protocols. The initial recommendation to restrict physical exertion in individuals with PH was based on its adverse impact on their clinical status. But clinicians have recently concentrated on the significance of physical exercise in those with PH. Consistent physical activity can enhance functional capacity, elevate quality of life (QoL), and increase prognosis and life expectancy as well. This literature review seeks to consolidate research about the impact of physical activity on NT-ProBNP levels in individuals with CHD-PH.